Factors associated with road safety behavior and road risk perceptions among parents of children aged 10 and 12 years at Rembau, Negeri Sembilan, Malaysia - Selvan, Hari Krishnan Tamil (2012)
A cross-sectional study was carried out at the district of Rembau, Negeri Sembilan to determine the prevalence and factors associated with the parental road risk perception and parental safe road behavior. Simple random sampling method was used for selection of respondents for the study. A total of 202 respondents participated in the research. Data was collected by face to face interview using a structured questionnaire from September to December, 2010. Descriptive, bivariate and multivariate analyses were carried out using P ASW Statistics version 18. Prevalence of perception of road as a very dangerous environment for children when they are not accompanied by adults is 21.3 % among the respondents while the prevalence of road safety behavior practice as always among the respondents is 29.2% when accompanying their children on the road. Three variables were found to be associated with parental road risk perceptions. They included ethnicity (p=0.04l), household income (p=0.043) and number of male children in the family (p= 0.028). On the other hand, education level of parents (p=O.O 12), occupational class (p=0.012), household income (p=0.033) and the existence of playground (p=0.014) appear to be associated with parental safe road behavior. Multiple linear regression analyses result shows that numbers of male children in the family (p=0.038) were found to be the contributing factor for parental road risk perception and the model shows that number of male children in the family contributes 2.5% of variation. The higher the number of male children in the family, the lower the parental road risk perception. Household income more than RM 1000 emerged as a significant (p=0.004) factor in parental safe road behavior. The model suggests that 7.0% of variation in the parental safe road behavior could be explained by this factor. Based on the model generated, for household income more than RM 1000, there will be increase of 1.827 safe road behavior score compare to parents' with household income less than RM 1000. In conclusion, the study accomplished all of its objectives. The findings from the research suggest that future intervention targeting parents to reduce the child road traffic crashes should be focused to parents of Indian ethnicity, low household income, high number of male children in the family, non-professional occupational class group and parents living in neighborhood without playground.